Predictive value of prognostic nutritional index for the long-term prognosis of elderly patients with fracture: a systematic review and meta-analysis - Bai, Bing; Liu, Xilin; Li, Hong (Frontiers in Nutrition, 2025)
ObjectivesTo present the most recent and comprehensive systematic review and meta-analysis assessing the predictive value of prognostic nutritional index (PNI) for the long-term outcomes of elderly patients with fractures.MethodsWe systematically searched PubMed, Cochrane, Embase and Web of Science up to July, 2025 for studies assessing the predictive value of PNI for the long-term prognosis of elderly patients with fractures. The primary outcome measured was mortality. Odds ratios (ORs) and 95% confidence intervals (CIs) were used for data pooling. Additionally, sensitivity and subgroup analyzes were performed to assess the stability of the results and identify potential sources of heterogeneity. All analyzes were performed using Review Manger 5.4 and STATA 15.1.ResultsEight studies encompassing 11,576 elderly individuals were included for meta-analysis. The meta-analysis demonstrated that mortality was notably lower in individuals with high PNI compared to those with low PNI (OR: 0.75; 95% CI: 0.66, 0.85; p < 0.0001). Subgroup analysis of mortality based on study design and PNI cut-off showed that the predictive value of PNI for mortality remained significant in prospective studies and those with a cut-off value ≥40. However, this association was not observed in retrospective studies or those with a cut-off below 40.ConclusionPNI can effectively predict the long-term mortality in elderly individuals with fractures. Considering the limitations of this article, future large-scale, multicenter prospective cohort studies are still required to evaluate the prognostic value of PNI in senior patients with fractures and its influencing factors.Systematic review registrationPROSPERO, identifier CRD420251047385.